MOODY’S CREDIT RATINGS AND THE STOCK MARKET PERFORMANCE OF PORTUGUESE RATED FIRMS - Pacheco, Luís (Journal of Advanced Studies in Finance; Vol 3 No 1 (2012): JASF Volume III Issue 1(5) Summer 2012, 2012)
Never has the issue of sovereign credit ratings attracted such an interest by policy and opinion makers, bankers and journalists, or even the public opinion, as witnessed in the last couple of years. In spite of being accused of contributing to the instability of financial markets, credit rating agencies undoubtedly have a role in financial markets, affecting its performance and guiding investors’ decisions. This paper analyzes the impact of the changes announced in Moody’s ratings over the performance of a set of rated firms quoted in the Portuguese stock market. Following an event study methodology, we collect ratings and outlook announcements by that major credit agency over the period 2006-2011. We find a significant response of share prices to changes in ratings, with that response anticipating the announcement. We think that could be explained by previous sovereign rating changes or to the contagion effects of a bearish market. When analyzing the period after January 2010, we observe a stronger reaction to announcements, which has understandably given the greater influence and market sensitivity to rating agencies.